Butyrate in broiler diets : - Moquet, Pierre C. A. (Wageningen University, 2018)
The release profile of experimental and commercially available butyrate feed additives was measured in an in vitro study. Butyrate derivatives having markedly different release profiles were used in two in vivo experiments to inverstigate the effect of butyrate presence in distinct GIT segments on digestive processes, microbiota composition and immune responses of broilers.